2014
DOI: 10.1002/qua.24679
|View full text |Cite
|
Sign up to set email alerts
|

Substitution effect on the intermolecular halogen and hydrogen bonds of the σ‐bonded fluorinated pyridine···XY/HX complexes (XY = F2, Cl2, ClF; HX = HF, HCl)

Abstract: Optimal structures, electronic and thermodynamic properties of the title complexes are presented. The stability of the hydrogen bonded systems is enhanced by the increasing dipole moments whereas in the halogen bonded systems it is also affected by the atom size in the diatomics. The consecutive addition of fluorine atoms to the pyridine moiety results in the decrease of the interaction energy for both types of the investigated bonds. The substitution on the meta sites in pyridine leads to more stable complexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…It is therefore the least likely to function as a halogen-bond donor. However, some theoretical calculations and experimental results indicate that F atoms can indeed work as halogen-bond donors and interact with electron-rich elements to form halogen-bond complexes under specific circumstances including F 2 or CN–F, , although their strengths are much weaker than other halogens.…”
Section: Directionality and Strength Of The σ-Hole Bond And π-Hole Bondmentioning
confidence: 99%
“…It is therefore the least likely to function as a halogen-bond donor. However, some theoretical calculations and experimental results indicate that F atoms can indeed work as halogen-bond donors and interact with electron-rich elements to form halogen-bond complexes under specific circumstances including F 2 or CN–F, , although their strengths are much weaker than other halogens.…”
Section: Directionality and Strength Of The σ-Hole Bond And π-Hole Bondmentioning
confidence: 99%
“…Recently, it has been shown that the halogen substitution changes drastically the structure and electronic states of molecules. Development of high performance switching device may be possible using the halogen substitution in the DNA base pair.…”
Section: Introductionmentioning
confidence: 99%
“…The aminopyridine and pyrimidine dimers are known as mimic models of DNA base pair with two hydrogen bonds between AP molecules. Ionization of (AP) 2 causes a proton transfer along the hydrogen bonds, and it forms a defect of hydrogen bond in DNA. Time scale of PT process was estimated to be 100–200 fs, which is a very fast process as a chemical reaction .…”
Section: Introductionmentioning
confidence: 99%